From help to hinderance: the rising overuse of ChatGPT by students - Roslan, Muhammad Azril (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Digital learning has undergone a significant transformation of the educational landscape in recent years, particularly with the global shift to online and hybrid learning paradigms. One of the most revolutionary instruments to arise in this era is ChatGPT, a conversational AI model developed by OpenAI. As students globally adopt digital solutions to enhance their education, AI tools such as ChatGPT continue to grow, despite some negative consequences. It is essential to examine the origins of ChatGPT to fully appreciate its present significance to digital learning fully. The quest commenced with GPT-1 in 2018, which was succeeded by GPT-2 in 2019, which garnered attention for its capacity to produce surprisingly sensible text. Nonetheless, it was GPT-3 in 2020 that completely embodied a turning point. GPT-3 has the capacity to generate essays, solve problems, summarise texts, and simulate human-like conversations on a scale that has never been observed before, with 175 billion parameters.